Case Report: A de novo CTNNB1 Nonsense Mutation Associated With Neurodevelopmental Disorder, Retinal Detachment, Polydactyly - KE, Zhongling; CHEN, Yanhui (Frontiers in Pediatrics, 2020)
CTNNB1 gene mutation was firstly reported related to intellectual disability in 2012, to explore the clinical phenotype and genotype characteristics of CTNNB1 mutation, we collected and analyzed the clinical data of a child with a neurodevelopmental disorder caused by a mutation of CTNNB1. The child had dysmorphic features, microcephaly, hypotonia，polydactyly, retinal detachment, and neurodevelopmental disorder, with a de novo mutation of CTNNB1 c.1603C > T, p.R535X. The patient was diagnosed as Neurodevelopmental disorder with spastic diplegia and visual defects (NEDSDV) and was given rehabilitation training. After 4 months of rehabilitation training, she improved in gross motor function. We found that CTNNB1 mutation can cause neurodevelopmental disorder, which could be accompanied by retinal detachment and polydactyly. The retinal detachment had only been reported in two Asian patients, and we firstly reported the phenotype of polydactyly in the CTNNB1 mutation. This report not only helps to expand the clinical phenotype spectrum of the CTNNB1 gene mutation but also prompts a new insight into genetic diagnosis in patients with a neurodevelopmental disorder, retinal detachment, and polydactyly.